The role of perceived barrier in the postpartum women's health promoting lifestyle: A partial mediator between self-efficacy and health promoting lifestyle - Khadijeh Hajimiri; Elham Shakibazadeh; Ali Asghar Haeri Mehrizi; Sakineh Shab-Bidar; Roya Sadeghi (Wolters Kluwer Medknow Publications, 2018)
Introduction: In recent decades, the focuses of health studies were mostly in middle-aged women, and few studies have investigated the lifestyle of women after delivery. The aim of this study was to determine the effects of both self-efficacy and perceived barriers on Iranian women health-promoting lifestyle (HPL) in the first 1 year after childbirth. Materials and Methods: Using a cross-sectional design, 310 women at first-year postpartum were surveyed in Zanjan (Iran) in 2016. The proportionate stratified random sampling method was carried out to select a participant. HPL has assessed with HPL profile II questionnaire. Self-efficacy was assessed using self-rated abilities for health practices scale. Perceived barriers were assessed by Barriers to Health-promoting Activities for Disabled Person scale. A meditational model was used to examine whether perceived barriers mediates between perceived self-efficacy and HPL. Results: The participants mean age was 29.82 (5.1) years, 53.9% were primiparous, and most of them were homemakers (82.9%). The mean total score of HPL was 2.50 (0.29). The relationship between HPL and self-efficacy was mediated by perceived barriers partially. Discussion: Self-efficacy, not only promotes women's HPL but also indirectly affect the women's lifestyle by reducing perceived barriers.